PENAGGULANGAN KEJAHATAN TEKNOLOGI INFORMASI (CYBER CRIME) YANG MENIMBULKAN KEGADUHAN DAN PERMUSUHAN MELALUI PENDEKATAN PENAL POLICY DI WILAYAH HUKUM POLRESTABES MEDAN - Yamirah Mandasari Saragih; Irma Fatmawati; Syaiful Asmi (Ensiklopedia of Journal, 2022)
One of the other important policies, namely the Law on Information and Electronic Transactions or Law number 11 of 2008 or UU ITE is a law that regulates information and electronic transactions, or information technology in general. The ITE Law, which has been in effect since April 2008, is indeed a breakthrough for the legal world in Indonesia, because for the first time the virtual world in Indonesia has a device. Because of its nature which contains the rules of the game in cyberspace, the ITE Law is also known as Cyber Law. When viewed from the content of the ITE Law, all important matters have been accommodated and regulated in the Law. The ITE Law is comprehensive enough to regulate electronic information and electronic transactions. Let's look at some of the material coverage of the ITE Law which is a new breakthrough. The ITE Law which recognizes that Electronic Signatures have the same legal force as conventional signatures (wet ink and stamp duty), electronic evidence is recognized as other evidence regulated in the Criminal Procedure Code, the ITE Law applies to everyone who commits a good legal act located in the territory of Indonesia or outside Indonesia, which has legal consequences in Indonesia. Dispute resolution can also be resolved by alternative dispute resolution methods or arbitration. There will be at least nine Government Regulations as implementing regulations for the ITE Law, so that this Law can run effectively.Keywords: Crime, Penal, Policy.